Infant health, cognitive performance and earnings: Evidence from inception of the welfare state in Sweden - Sonia R. Bhalotra; Martin Karlsson; Therese Nilsson; Nina Schwarz (University of Essex, Institute for Social and Economic Research (ISER), 2019)
We identify earnings impacts of exposure to an infant health intervention in Sweden, using individual linked administrative data to trace potential mechanisms. Leveraging quasi-random variation in eligibility, we estimate that exposure was associated with higher test scores in primary school for boys and girls, with a different distribution of gains, only girls being more likely to score in the top quintile. Subsequent gains, in secondary schooling, employment, and earnings, are restricted to girls. We argue that the differential gains for women accrued from both skills and opportunities, expansion of the welfare state having created unprecedented employment opportunities for women.
Keywords: I15; I18; H41; 330; Infant health; early life interventions; cognitive skills; education; earnings; occupational choice; programme evaluation; Sweden